The Long-Term Spectrum of Neurological Sequelae After Stroke: A Systematic Review of Multidimensional Outcomes - Chairunnisa; Ikchan Malik Napitupulu (The International Journal of Medical Science and Health Research, 2025)
Introduction Stroke is the world's second leading cause of death and a dominant driver of long-term disability globally. The acute vascular insult initiates irreversible brain damage, characterized by the rapid loss of approximately 1.9 million neurons per minute during compromised cerebral perfusion (Lee et al., 2024). This systematic review evaluates the prevalence, trajectory, and key predictors of chronic neurological, cognitive, and psychosocial deficits following stroke, focusing on the multi-dimensional burden up to 10 years post-event. Methods This systematic review was conducted in adherence to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA 2020) guidelines (PRISMA 2020). We included longitudinal cohort studies and population registers that assessed outcomes at least six months post-stroke. Methodological rigor was ensured by applying the ROBINS-I Version 2 tool to evaluate the risk of bias across the included non-randomized studies (ROBINS-I V2). Results Fifteen high-quality longitudinal studies were included, aggregating data on over 15,000 stroke survivors. Neurological and functional deficits demonstrated a recovery plateau by one year, after which they remained chronically stable (Wolfe et al., 2011). Rates of severe disability (Barthel Index <15) stabilized at approximately 11.0%, and general cognitive impairment persisted at 18.0% one year post-stroke (Wolfe et al., 2011). The annual incidence of new dementia was found to be 1.7%, effectively doubling the risk compared to the non-stroke population (Chen et al., 2018). Critically, socioeconomic status (SES) emerged as a powerful prognostic determinant. Lower income was independently associated with poorer executive function and a lower total brain volume to total intracranial volume (TBV/TICV) ratio (Lee et al., 2024), while living in a socioeconomically deprived neighborhood increased the odds of a poor functional outcome by 55% (OR, 1.55; 95% CI, 1.25–1.92) (Robinson et al., 2024). Discussion The high and persistent prevalence of functional and psychosocial deficits, including anxiety (35.0-40.0%) and depression (31.0-35.0%), confirms stroke's classification as a chronic, long-term condition (Wolfe et al., 2011). The analysis suggests that socioeconomic vulnerability may accelerate underlying neurodegeneration, reducing the brain's structural resilience (TBV/TICV) and impairing neuroplastic potential, thereby explaining the observed disparity in chronic outcomes (Lee et al., 2024). Effective management strategies must target integrated rehabilitation and address the systemic social determinants that modulate neurological recovery. Conclusion Long-term neurological deficits after stroke are highly prevalent and persistently debilitating. The significant and negative association between lower socioeconomic status and neurological outcomes necessitates policy interventions to mitigate these social determinants of health and restructure care toward a chronic disease model.